Concrete protection method and concrete protection kit
By using cleaning tape with specific light-transmissive mittance and adhesion characteristics in low-temperature environments to remove dust from concrete surfaces and applying adhesion layers under specific conditions, the problem of reduced adhesion capacity in low-temperature environments is solved, and effective dust removal and protective layer adhesion is achieved.
Patent Information
- Application Number
- JP2024164355
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-26
- Filing Date
- 2024-09-20
- Publication Date
- 2025-04-08
AI Technical Summary
In low temperature environments, the adhesion ability of the structural protective sheet is reduced, making it difficult to remove dust, affecting the effectiveness of the protective layer.
Using a method including cleaning steps, dust is removed using cleaning tape with specific light transmissive mittance and adhesion characteristics, and then the adhesion layer is applied to the cleaned concrete surface under conditions that meet the specific relationship.
Effectively remove dust on the concrete surface in low-temperature environments, improve the adhesion of the adhesion layer, and ensure the effectiveness and durability of the protective layer.
Smart Images

Figure 2025056766000004 
Figure 2025056766000005 
Figure 2025056766000006
Abstract
Description
[Technical field]
[0001] The present invention relates to a concrete protection method and a concrete protection kit. [Background technology]
[0002] Large structures such as viaducts, tunnels, bridges, steel towers, and tanks are often constructed by combining steel and concrete materials. Steel and concrete materials corrode over time, causing rust, cracks, and other defects. When the corrosion progresses, the corroded areas may be repaired, for example, by applying paint or adhesive to the surface of the structure. However, such repair methods require complicated work processes and require a considerable amount of time before the actual repair work can begin. Therefore, there is a problem that the rust may progress further in the corroded areas or pieces of concrete may fall from the corroded areas before the repair work can actually begin.
[0003] As a method for simplifying the process of repairing corroded areas, it is known that a sheet is attached to the corroded area to suppress the progress of corrosion. For example, the structure protection sheet described in Patent Document 1 is known as a conventional technique as such a sheet. The structure protection sheet described in Patent Document 1 is provided with an adhesive layer, a hardened polymer cement layer, and a resin layer in this order. By using the structure protection sheet described in Patent Document 1, the construction time required for providing a protective layer on the surface of a structure such as concrete can be significantly reduced. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2022-184760 A Summary of the Invention [Problem to be solved by the invention]
[0005] If dust is present on the surface of a structure, the dust inhibits adhesion of the structure protection sheet to the structure. In particular, in a low-temperature environment, the structure protection sheet becomes hard and its ability to follow dust attached to the surface of the structure deteriorates, so that if dust is present on the surface of the structure, the adhesion of the structure protection sheet to the structure is significantly reduced. For this reason, it is necessary to remove the dust present on the surface of the structure before attaching the structure protection sheet to the surface of the structure. However, Patent Document 1 does not disclose how much dust should be removed from the surface of the structure when attaching the structure protection sheet to the structure. For this reason, the removal of the dust present on the surface of the structure was insufficient, and the adhesion of the structure protection sheet to the structure was reduced, or the work of removing the dust present on the surface of the structure was performed more than necessary, which extended the construction period for providing a protective layer on the surface of the structure. Therefore, an object of the present invention is to provide a concrete protection method and a concrete protection kit that can properly remove dust adhering to the surface of a structure, particularly a concrete surface, in a low-temperature environment before attaching an adhesive sheet for protecting the concrete to the surface of the structure, particularly the surface of concrete. [Means for solving the problem]
[0006] Means for Solving the Problems The present inventors have conducted extensive research and found that the above-mentioned problems can be solved by providing the following configuration, and have completed the present invention. The present invention provides the following [1] to
[11] . [1] A method for protecting concrete by attaching an adhesive sheet to the concrete, comprising: a cleaning step of cleaning the surface of the concrete to which the adhesive sheet is to be attached, and removing dust adhering to the surface from the surface; and The method includes a step of attaching the adhesive sheet to the surface of the concrete cleaned by the cleaning step, The cleaning step is a concrete protection method in which an oriented polypropylene tape having a total light transmittance of 86% or more is attached to the surface of the concrete, and cleaning is performed until the relationship of the following formula (1) is satisfied, where the visible light transmittance of the oriented polypropylene tape after the oriented polypropylene tape is peeled off from the surface of the concrete is a%, and the 90° adhesive strength of the adhesive sheet to a mortar board at a temperature of 0°C in accordance with JIS R 5201 is bN / 25mm. a+b≧110 (1) [2] The concrete protection method described in [1] above, wherein the visible light transmittance of the oriented polypropylene tape is the visible light transmittance measured using a handheld transmittance meter. [3] A concrete protection method as described in [1] or [2] above, in which the surface of the concrete before the cleaning process is covered with an oriented polypropylene tape having a total light transmittance of 86% or more, and the total light transmittance of the oriented polypropylene tape after peeling it off is 80% or less. [4] The concrete protection method according to any one of [1] to [3] above, wherein the cleaning step comprises adhering the dust adhering to the surface of the concrete to an adhesive cleaning tape having an adhesive layer, thereby removing the dust from the surface. [5] The method for protecting concrete according to the above [4], wherein the thickness of the adhesive layer of the cleaning adhesive tape is 20 to 80 μm. [6] The method for protecting concrete according to the above [4] or [5], wherein the adhesive layer of the cleaning adhesive tape has a gel fraction of 70% or less. [7] A concrete protection method according to any one of the above [4] to [6], wherein the difference between the tensile load of the cleaning adhesive tape when elongated by 2.5% and the tensile load when elongated by 0.5% is 40 N / 24 mm or less. [8] The concrete protection method according to any one of the above [4] to [7], wherein the cleaning adhesive tape has a 180° adhesive strength of 5 N / 25 mm or more. [9] The concrete protection method according to any one of the above [1] to [8], wherein the adhesive sheet has a thickness of 100 to 2500 μm.
[10] The pressure-sensitive adhesive sheet has a pressure-sensitive adhesive layer, The concrete protection method according to any one of the above [1] to [9], wherein the pressure-sensitive adhesive layer of the pressure-sensitive adhesive sheet has a storage modulus of 200,000 to 2,500,000 Pa at 0° C.
[11] A concrete protection kit including an adhesive tape for cleaning concrete and an adhesive sheet for protecting the concrete, The cleaning adhesive tape adheres to and removes dust adhering to the surface of the concrete, thereby cleaning the concrete; The adhesive sheet is a concrete protection kit that protects the concrete by being attached to the surface of the concrete that has been cleaned with the cleaning adhesive tape. Effect of the Invention
[0007] According to the present invention, a concrete protection method and a concrete protection kit can be provided that can properly remove dust adhering to the surface of concrete before attaching an adhesive sheet for protecting the concrete to the surface of the concrete in a low-temperature environment. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 is a schematic diagram showing an example of the configuration of a pressure-sensitive adhesive sheet used in the attachment step. [Diagram 2] FIG. 2 is a schematic diagram showing an example of the configuration of a pressure-sensitive adhesive sheet used in the attachment step. [Diagram 3] FIG. 3 is a schematic diagram showing an example of the configuration of a pressure-sensitive adhesive sheet used in the attachment step. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] [Concrete protection method] The concrete protection method of the present invention is a method for protecting concrete by attaching an adhesive sheet to the concrete. The concrete protection method of the present invention includes a cleaning step of cleaning the surface of the concrete to which the adhesive sheet is to be attached and removing dust adhering to the surface from the surface, and an attachment step of attaching the adhesive sheet to the surface of the concrete cleaned in the cleaning step.
[0010] (Cleaning process) As described above, in the cleaning process, the surface of the concrete to which the adhesive sheet is to be attached is cleaned to remove dust adhering to the surface. In the cleaning process, cleaning is continued until the relationship of the following formula (1) is satisfied. a+b≧110 (1) Here, a is the visible light transmittance (%) of an oriented polypropylene tape with a total light transmittance of 86% or more attached to the surface of concrete and then peeled off from the surface of concrete, and b is the 90° adhesive strength (N / 25mm) of the adhesive sheet to a mortar board at a temperature of 0°C according to JIS R 5201. If the concrete surface is not cleaned until the relationship of the above formula (1) is satisfied, the adhesive sheet may not adhere sufficiently to the concrete surface in a low-temperature environment, and the concrete may not be sufficiently protected in a low-temperature environment. From this viewpoint, in the cleaning process, cleaning is preferably performed until the above value of (a+b) satisfies the relationship of the following formula (1a), more preferably until the following relationship of formula (1b) is satisfied, and even more preferably until the following relationship of formula (1c) is satisfied. Note that the higher the value of (a+b), the better, and the upper limit of the range of the value of (a+b) is not particularly limited, but the value of (a+b) is practically about 200 or less. a+b≧112 (1a) a+b≧116 (1b) a+b≧120 (1c) It is preferable to use the stretched polypropylene tape described in the Examples below. The total light transmittance of the stretched polypropylene tape, the visible light transmittance of the stretched polypropylene tape, and the 90° adhesive strength of the adhesive sheet to a mortar board at a temperature of 0°C according to JIS R 5201 can be measured by the method described in the Examples below. From the viewpoint of ease of measurement on site, it is preferable to measure the visible light transmittance of the stretched polypropylene tape with a handy transmittance meter. In the cleaning process, the value of a may be actually measured to confirm that the value of (a+b) is within the above range. However, it is sufficient to perform cleaning so that the value of (a+b) is within the above range, and it is not necessary to actually measure the value of a.
[0011] It is preferable that the concrete surface before carrying out the cleaning step is one in which an oriented polypropylene tape having a total light transmittance of 86% or more is attached to the surface, and the total light transmittance of the oriented polypropylene tape after peeling off is 80% or less. A concrete surface having a total light transmittance of 80% or less has a large amount of dust adhering thereto, so cleaning of the concrete surface is highly necessary, and the concrete surface can be protected more effectively by applying the protection method of the present invention.
[0012] The cleaning method of the concrete surface in the cleaning process is not particularly limited as long as the dust adhering to the concrete surface can be removed from the surface. For example, the dust adhering to the concrete surface may be removed by spraying compressed air or water onto the concrete surface. However, it is preferable to remove the dust adhering to the concrete surface using a cleaning adhesive tape described later.
[0013] <Cleaning adhesive tape> The material used in the cleaning process to remove dust adhering to the surface of concrete is preferably a cleaning adhesive tape having an adhesive layer. By adhering the dust adhering to the surface of concrete to the cleaning adhesive tape, the dust can be removed from the surface of concrete. This makes it possible to clean the surface of concrete with a simple operation. The cleaning adhesive tape may also be the aforementioned stretched polypropylene tape having a total light transmittance of 86% or more.
[0014] <Thickness of adhesive layer of cleaning tape> The thickness of the adhesive layer of the cleaning adhesive tape is preferably 20 to 80 μm. When the thickness of the adhesive layer of the cleaning adhesive tape is 20 μm or more, dust adhering to the surface of concrete can be removed more reliably. When the thickness of the adhesive layer of the cleaning adhesive tape is 80 μm or less, the cleaning adhesive tape attached to the surface of concrete can be easily peeled off from the surface of concrete. From this viewpoint, the thickness of the adhesive layer of the cleaning adhesive tape is more preferably 25 to 70 μm, even more preferably 30 to 65 μm, and even more preferably 35 to 60 μm.
[0015] <Gel fraction of adhesive layer of cleaning tape> The gel fraction of the adhesive layer of the cleaning adhesive tape is preferably 70% or less. When the gel fraction of the adhesive layer of the cleaning adhesive tape is 70% or less, the adhesive layer has a higher ability to follow dust adhering to the concrete surface, and the dust adhering to the concrete surface can be more reliably removed. From this viewpoint, the gel fraction of the adhesive layer of the cleaning adhesive tape is more preferably 60% or less, even more preferably 55% or less, and even more preferably 50% or less. The lower limit of the range of the gel fraction of the adhesive layer of the cleaning adhesive tape is not particularly limited, but is preferably 20%, more preferably 30%, from the viewpoint of preventing the adhesive layer from remaining on the concrete surface after the cleaning adhesive tape is peeled off from the concrete surface. The gel fraction can be measured by the method described in the Examples below.
[0016] <Difference in tensile load of cleaning adhesive tape> The difference between the tensile load of the cleaning adhesive tape when it is elongated by 2.5% and the tensile load when it is elongated by 0.5% is preferably 40N / 24mm or less. When the difference between the tensile load of the cleaning adhesive tape when it is elongated by 2.5% and the tensile load when it is elongated by 0.5% is 40N / 24mm or less, the flexibility of the cleaning adhesive tape is more maintained. As a result, the cleaning adhesive tape is more likely to follow the dust adhering to the surface of the concrete, and the dust adhering to the surface of the concrete can be more reliably removed. From this viewpoint, the difference between the tensile load of the cleaning adhesive tape when it is elongated by 2.5% and the tensile load when it is elongated by 0.5% is more preferably 35N / 24mm or less, even more preferably 30N / 24mm or less, and even more preferably 25N / 24mm or less. The lower limit of the range of the difference between the tensile load when the cleaning adhesive tape is elongated by 2.5% and the tensile load when the cleaning adhesive tape is elongated by 0.5% is not particularly limited, but is preferably 10 N / 24 mm from the viewpoint of workability. The tensile load of the cleaning adhesive tape can be measured by the method described in the Examples below. The difference in the tensile load can be adjusted, for example, by the material and thickness of the substrate of the cleaning adhesive tape.
[0017] <180° adhesive strength of cleaning tape> The 180° adhesive strength of the cleaning adhesive tape is preferably 5N / 25mm or more. When the 180° adhesive strength of the cleaning adhesive tape is 5N / 25mm or more, dust attached to the surface of the concrete can be removed more reliably. From this viewpoint, the 180° adhesive strength of the cleaning adhesive tape is more preferably 6N / 25mm or more, even more preferably 7N / 25mm or more, and even more preferably 8N / 25mm or more. The upper limit of the range of the 180° adhesive strength of the cleaning adhesive tape is not particularly limited, but is preferably 30N / 25mm, more preferably 20N / 25mm, from the viewpoint of preventing the adhesive layer from remaining on the surface of the concrete after the cleaning adhesive tape is peeled off from the surface of the concrete. The 180° adhesive strength of the cleaning adhesive tape can be measured by the method described in the Examples below. The 180° adhesive strength of the cleaning adhesive tape can be adjusted, for example, by the material, thickness, gel fraction, etc. of the adhesive layer.
[0018] <Adhesive> The adhesive layer of the cleaning adhesive tape is preferably formed of an adhesive. The type of adhesive is not particularly limited, but for example, an adhesive that can be used for the adhesive sheet described below can be used. The adhesive constituting the adhesive layer is preferably an acrylic adhesive.
[0019] <Base material> The cleaning adhesive tape preferably has a substrate. The substrate in the cleaning adhesive tape is not particularly limited, but may be, for example, a substrate that can be used in the adhesive sheet described below. The substrate in the cleaning adhesive tape is preferably a stretched polypropylene sheet and a polyester woven sheet, more preferably a biaxially stretched polypropylene sheet and a PET (polyethylene terephthalate) woven sheet.
[0020] The cleaning step is preferably performed by attaching a cleaning adhesive tape to the surface of the concrete and then peeling it off from the surface of the concrete, but the number of times of application to the same surface of the concrete may be one or more. The number of times of application is defined as one time when the cleaning adhesive tape is attached and then peeled off. The upper limit of the number of times of application is not particularly limited, and is, for example, 10 times, but from the viewpoint of workability, it is preferably 5 times, and more preferably 3 times.
[0021] (Attachment process) As described above, in the attaching step, the adhesive sheet is attached to the surface of the concrete that has been cleaned in the cleaning step, thereby protecting the surface of the concrete. <Adhesive sheet> The pressure-sensitive adhesive sheet used in the attachment step preferably comprises a substrate and a pressure-sensitive adhesive layer provided on one surface of the substrate.
[0022] <Base material> The substrate in the pressure-sensitive adhesive sheet used in the attachment step is not particularly limited, but examples thereof include sheet-like materials such as resin films, nonwoven fabrics, woven fabrics, and metal foils. Examples of the resin film include polyethylene resin films, polypropylene resin films, acrylic resin films, fluorine resin films, polyvinyl chloride resin films, polycarbonate resin films, AES resin films, and ASA resin films. The nonwoven fabric is made of synthetic resin fibers, such as polyamide, polyester, polyacrylic, polyolefin, or polyurethane. The woven fabric is made of synthetic resin fibers such as polyamide, polyester, polyacrylic, polyolefin, and polyurethane. Examples of metal foils include metal foils of iron and its alloys, metal foils of metals having a lower electric potential than iron, such as chromium, zinc, titanium, aluminum, and magnesium, and metal foils of metals having a higher electric potential than iron, such as gold, silver, copper, tin, nickel, and cobalt. These sheet-like materials can be used alone or in combination of two or more. From the viewpoint of protecting the pressure-sensitive adhesive layer, the substrate is preferably a resin film, more preferably a PET film or a fluororesin film. In addition, in the case of a resin film, the interfacial strength can be easily increased by modifying the surface of the substrate by corona treatment or by providing an undercoat layer.
[0023] The thickness of the substrate is not particularly limited, but is preferably 10 to 500 μm, more preferably 30 to 400 μm, and further preferably 40 to 300 μm. When the substrate has a thickness of 10 μm or more, it can function as a support. When the substrate has a thickness of 500 μm or less, it is easy to increase the adhesion to concrete structures.
[0024] The surface of the substrate on the side of the adhesive layer may be surface-modified by corona treatment. This can further increase the interfacial strength between the substrate and the adhesive layer in the concrete repair tape. The treatment intensity when carrying out the corona treatment is, for example, 0.05 to 0.5 kW, and the conveying speed is, for example, 0.5 to 20 m / min.
[0025] <Undercoat layer> The pressure-sensitive adhesive sheet used in the attachment step may further include an undercoat layer on the surface of the substrate facing the pressure-sensitive adhesive layer, thereby further improving the interfacial strength between the substrate and the pressure-sensitive adhesive layer. Examples of the polymer constituting the undercoat layer include aminoethylated acrylic polymer, polyethyleneimine, polyurethane water dispersion, isocyanate-based compounds, modified polybutadiene, and organic titanate-based compounds. Aminoethylated acrylic polymer is a primary amino group-containing acrylic polymer with polyethyleneimine grafted to the side chain. Commercially available aminoethylated acrylic polymers include "Polyment NK-350" manufactured by Nippon Shokubai Co., Ltd. Polyethyleneimine is a water-soluble polymer obtained by polymerizing ethyleneimine. Commercially available polyethyleneimine products include "Epomin P-1000" and "Epomin P-3000" manufactured by Nippon Shokubai Co., Ltd. Polyurethane water dispersions are self-dispersing polyurethane resins that have been given a small amount of hydrophilic groups or hydrophilic segments, or hydrophobic polyurethane resins that have been forcibly emulsified with a surfactant. Commercially available polyurethane water dispersions include "Superflex Series" manufactured by Daiichi Kogyo Seiyaku Co., Ltd. Of these polymers, aminoethylated acrylic polymers and polyethyleneimines are preferred from the viewpoint of the interfacial strength between the substrate and the pressure-sensitive adhesive layer. The undercoat can be formed by applying an undercoat paint containing the above-mentioned polymer to a substrate, and drying it as necessary.
[0026] <Amount of application> The coating weight (wet) of the undercoat layer is preferably 2 g / m 2 The coating amount (wet) is 2g / m 2 More than 20g / m 2 By setting the coating amount (wet) of the undercoat layer to 4 g / m or less, the interfacial strength between the substrate and the pressure-sensitive adhesive layer can be further improved. From this viewpoint, the coating amount (wet) of the undercoat layer is more preferably 4 g / m or less. 2 More than 15g / m 2 More preferably, it is 7 g / m or less. 2 More than 12g / m 2 The following is the result.
[0027] <Adhesive layer> The adhesive layer is preferably formed of an adhesive. The type of adhesive is not particularly limited, but examples thereof include acrylic adhesives, rubber adhesives, urethane adhesives, and silicone adhesives. These may be used alone or in combination. Among these, the pressure-sensitive adhesive layer is preferably formed from an acrylic pressure-sensitive adhesive.
[0028] <Acrylic adhesive> The acrylic pressure-sensitive adhesive is a pressure-sensitive adhesive containing an acrylic polymer obtained by polymerizing a polymerizable monomer including a (meth)acrylic acid alkyl ester monomer (A). In this specification, the term "(meth)acrylic acid alkyl ester" refers to a concept including both acrylic acid alkyl ester and methacrylic acid alkyl ester, and the same applies to other similar terms. In addition, the term "polymerizable monomer" refers to a concept that can include not only a compound having no repeating unit, but also a monomer itself having a repeating unit, such as the olefin polymer (C) described later, as long as it is a compound that copolymerizes with the (meth)acrylic acid alkyl ester monomer (A).
[0029] ((Meth)acrylic acid alkyl ester monomer (A)) The (meth)acrylic acid alkyl ester monomer (A) is an ester of (meth)acrylic acid and an aliphatic alcohol, and is preferably an alkyl ester derived from an aliphatic alcohol in which the carbon number of the alkyl group of the aliphatic alcohol is preferably 2 to 14, more preferably 4 to 10. When the carbon number of the alkyl group is within this range, the adhesive strength is easily increased, and the storage modulus at 23°C of the adhesive described below is easily adjusted to a predetermined range.
[0030] Specific examples of the (meth)acrylic acid alkyl ester monomer (A) include ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, and tetradecyl (meth)acrylate. Among these, n-butyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and n-octyl (meth)acrylate are preferred, with 2-ethylhexyl (meth)acrylate being more preferred. The (meth)acrylic acid alkyl ester monomers may be used alone or in combination of two or more kinds.
[0031] The constituent unit derived from the (meth)acrylic acid alkyl ester monomer (A) constitutes the main component in the adhesive layer, and its content is generally 30% by mass or more, preferably 50% by mass or more, more preferably 70% by mass or more based on the total amount of the adhesive layer. In this way, by increasing the content of the (meth)acrylic acid alkyl ester monomer (A), it is possible to impart the desired adhesive strength to the adhesive layer. In addition, the content of the constituent unit derived from the (meth)acrylic acid alkyl ester monomer (A) is, for example, 97% by mass or less, preferably 95% by mass or less, more preferably 90% by mass or less in order to contain a certain amount or more of other components. The content of the constituent unit derived from the (meth)acrylic acid alkyl ester monomer (A) in the pressure-sensitive adhesive layer is substantially the same as the content of the (meth)acrylic acid alkyl ester monomer (A) in the pressure-sensitive adhesive composition described below, and can be expressed interchangeably. The same applies to components other than the component (A), such as the components (B) and (C) described below.
[0032] <Polymerizable monomer containing polar group (B)> The polymerizable monomer preferably contains a polar group-containing polymerizable monomer (B) in addition to the (meth)acrylic acid alkyl ester monomer (A). The polar group-containing polymerizable monomer (B) is not particularly limited as long as it has a polar group and is polymerizable, and is, for example, a monomer having a polar group and a vinyl group (polar group-containing vinyl monomer). By using the polar group-containing polymerizable monomer (B), it becomes easier to improve the adhesive strength to the adherend. Examples of the polar group-containing polymerizable monomer (B) include polymerizable monomers having a carboxyl group, such as vinyl carboxylates (vinyl acetate), carboxylic acids (meth)acrylic acid, itaconic acid, and their anhydrides, polymerizable monomers having a hydroxyl group, such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, caprolactone-modified (meth)acrylate, polyoxyethylene (meth)acrylate, and polyoxypropylene (meth)acrylate, and nitrogen-containing polymerizable monomers, such as (meth)acrylonitrile, N-vinylpyrrolidone, N-vinylcaprolactam, N-vinyllaurolactam, (meth)acryloylmorpholine, (meth)acrylamide, dimethyl(meth)acrylamide, diethyl(meth)acrylamide, ethylmethyl(meth)acrylamide, N-methylol(meth)acrylamide, N-butoxymethyl(meth)acrylamide, and dimethylaminomethyl(meth)acrylate. Among these, preferred are polymerizable monomers having a carboxyl group, such as carboxylic acids such as (meth)acrylic acid and itaconic acid, and their anhydrides, as well as nitrogen-containing polymerizable monomers such as (meth)acryloylmorpholine and dimethyl(meth)acrylamide, more preferred are (meth)acrylic acid, (meth)acryloylmorpholine and dimethyl(meth)acrylamide, and even more preferred are acrylic acid, acryloylmorpholine and dimethylacrylamide. These polar group-containing polymerizable monomers (B) may be used alone or in combination of two or more.
[0033] When the polar group-containing polymerizable monomer (B) is used, the content of the constitutional unit derived from the polar group-containing polymerizable monomer (B) in the adhesive layer is preferably 0.1 to 15 parts by mass, more preferably 0.5 to 9 parts by mass, even more preferably 0.5 to 7 parts by mass, and even more preferably 1 to 5 parts by mass, based on 100 parts by mass of the constitutional unit derived from the (meth)acrylic acid alkyl ester monomer (A). By setting the content of the polar group-containing polymerizable monomer (B) within such a range, the adhesive strength of the concrete repair tape is easily improved.
[0034] <Olefin polymer (C)> The polymerizable monomer preferably further contains an olefin polymer (C) having a polymerizable bond at one end. By using such an olefin polymer (C), the adhesive strength of the concrete repair tape can be easily improved. The polymerizable bond means an unsaturated carbon-carbon bond capable of polymerizing with a polymerizable monomer, and examples thereof include an unsaturated double bond, and preferably a (meth)acryloyl group. The olefin polymer (C) may be a polyolefin having a (meth)acryloyl group at one end. The polyolefin is a polymer of an aliphatic hydrocarbon compound having a double bond, such as ethylene, propylene, butane, butadiene, isoprene, or the like, or a hydrogenated product thereof.
[0035] Examples of polyolefins having a (meth)acryloyl group at one end include polyethylene having a (meth)acryloyl group at one end, which is prepared by reacting polyethylene having an epoxy group at one end with (meth)acrylic acid. In addition, examples include polybutadiene having a (meth)acryloyl group at one end or a hydrogenated product thereof, and examples of commercially available products thereof include "L-1253" manufactured by Kuraray Co., Ltd.
[0036] The number average molecular weight of the olefin polymer (C) is preferably 500 to 20000, more preferably 1000 to 10000. The number average molecular weight may be measured by gel permeation chromatography (GPC) and calculated using a calibration curve of standard polystyrene. In addition, the content of the structural unit derived from the olefin polymer (C) in the pressure-sensitive adhesive layer is preferably 1 to 20 parts by mass, more preferably 2 to 15 parts by mass, and even more preferably 4 to 12 parts by mass, per 100 parts by mass of the structural unit derived from the (meth)acrylic acid alkyl ester monomer (A).
[0037] <Crosslinking agent (D)> The polymerizable monomer preferably further contains a crosslinking agent. Examples of the crosslinking agent include a polyfunctional monomer having two or more vinyl groups, and preferably a polyfunctional (meth)acrylate having two or more (meth)acryloyl groups. The use of a polyfunctional monomer makes it easier to adjust the adhesive strength of the adhesive layer to an appropriate range. The polyfunctional (meth)acrylate is not particularly limited, and examples thereof include bifunctional alkyl (meth)acrylates such as hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, ethoxylated bisphenol A di(meth)acrylate, tris(2-hydroxyethyl)isocyanurate triacrylate, ethoxylated trimethylolpropane triacrylate, proxied trimethylolpropane triacrylate, proxied glyceryl triacrylate, neopentyl glycol adipate diacrylate, and the like, as well as polymers such as polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, and liquid hydrogenated 1,2-polybutadiene di(meth)acrylate. Among these polyfunctional (meth)acrylates, polymers are preferred, and liquid hydrogenated 1,2-polybutadiene diacrylate is more preferred. Commercially available liquid hydrogenated 1,2-polybutadiene diacrylates include "TEAI-1000" manufactured by Nippon Soda Co., Ltd. In addition, bifunctional alkyl (meth)acrylates are also preferred, and commercially available products include A-HD-N of the NK Ester series manufactured by Shin-Nakamura Chemical Co., Ltd. The content of the structural unit derived from the crosslinking agent in the pressure-sensitive adhesive layer is preferably 0.005 to 0.1 parts by mass, more preferably 0.01 to 0.09 parts by mass, and even more preferably 0.02 to 0.08 parts by mass, per 100 parts by mass of the structural unit derived from the (meth)acrylic acid alkyl ester monomer (A).
[0038] <Tackifier resin> The acrylic adhesive may contain a tackifier resin from the viewpoint of improving adhesive strength. As the tackifier resin, a tackifier resin having low polymerization inhibition properties, such as hydrogenated terpene resin, hydrogenated rosin, disproportionated rosin resin, petroleum resin, etc., is preferable. Among these, hydrogenated tackifier resins are preferable because tackifier resins having many double bonds inhibit polymerization reactions, and hydrogenated petroleum resins are particularly preferable. From the viewpoint of improving the cohesive strength and adhesive strength of the adhesive, the softening point of the tackifier resin may be about 95° C. or higher, but preferably includes one that is 120° C. or higher, and for example, one that is 95° C. or higher and lower than 120° C. may be used in combination with one that is 120° C. or higher and 150° C. or lower. The softening point may be measured by the ring and ball method specified in JIS K2207. The content of the tackifier resin in the acrylic adhesive is preferably 3 to 40 parts by mass, more preferably 5 to 35 parts by mass, and even more preferably 7 to 25 parts by mass, per 100 parts by mass of the structural unit derived from the (meth)acrylic acid alkyl ester monomer (A).
[0039] <Fine particles> The acrylic adhesive may contain fine particles, which can improve the adhesive strength. Examples of the fine particles include inorganic hollow particles such as glass balloons, shirasu balloons, and fly ash balloons; organic hollow particles made of polymethyl methacrylate, acrylonitrile-vinylidene chloride copolymers, polystyrene, and phenolic resins; inorganic fine particles such as glass beads, silica beads, and synthetic mica; and organic fine particles such as ethyl polyacrylate, polyurethane, polyethylene, and polypropylene. The content of the fine particles in the acrylic pressure-sensitive adhesive is preferably 0.1 to 15 parts by mass, more preferably 0.5 to 10 parts by mass, and even more preferably 0.7 to 7 parts by mass, based on 100 parts by mass of the structural units derived from the (meth)acrylic acid alkyl ester monomer (A).
[0040] <Other ingredients> The acrylic adhesive used in the adhesive layer may contain, in addition to the components described above, various additives conventionally used in adhesives, such as plasticizers, softeners, pigments, dyes, polymerization initiators, flame retardants, and thickeners.
[0041] <Method of manufacturing acrylic adhesive and adhesive layer> The acrylic adhesive can be obtained by irradiating the adhesive composition containing the above-mentioned polymerizable monomer with light to polymerize the polymerizable monomer. The adhesive composition may also contain at least one of the above-mentioned tackifier resin, fine particles, and other components, as necessary. More specifically, first, the polymerizable monomer, the tackifier resin which is blended as required, the fine particles, and other components are charged into a reaction vessel such as a glass vessel and mixed to obtain a pressure-sensitive adhesive composition. Next, in order to remove dissolved oxygen in the pressure-sensitive adhesive composition, an inert gas such as nitrogen gas is generally supplied to purge the oxygen. Then, the pressure-sensitive adhesive composition is applied onto a release sheet, or onto a support such as a resin film, woven fabric, or nonwoven fabric, and then irradiated with light to polymerize the polymerizable monomer, thereby obtaining a pressure-sensitive adhesive layer. The steps from coating or impregnation with the pressure-sensitive adhesive composition to the step of irradiating with light are preferably carried out in an inert gas atmosphere or in a state in which oxygen is blocked by a film or the like. In the present production method, the pressure-sensitive adhesive composition obtained by mixing the components may be pre-polymerized before being applied to a release sheet, a support or the like in order to increase the viscosity.
[0042] <Rubber-based adhesive> Next, the rubber-based adhesive used in the adhesive layer will be described. The rubber-based adhesive contains a rubber component and a tackifier resin, and it is preferable to use a styrene-isoprene block copolymer as the rubber component. The styrene-isoprene block copolymer has a diblock ratio of preferably 25 to 70% by mass, more preferably 30 to 65% by mass, and even more preferably 45 to 60% by weight. Here, the diblock refers to a diblock consisting of styrene and isoprene. By setting the diblock ratio within the above range, it becomes easier to increase the adhesive strength. In addition to the diblock, the styrene-isoprene block copolymer also contains one having three or more blocks, such as a triblock consisting of a styrene, isoprene, and styrene block.
[0043] The amount of styrene in the styrene-isoprene block copolymer is not particularly limited, but is preferably 14 to 24% by mass, and more preferably 15 to 18% by mass. If the amount of styrene is 14% by mass or more, the adhesive tends to have high cohesiveness. If the amount of styrene is 24% by mass or less, the cohesive strength becomes moderate and adhesive strength is easily expressed. The molecular weight of the styrene-isoprene block copolymer is not particularly limited, but the mass average molecular weight is preferably 100,000 to 400,000, and more preferably 150,000 to 250,000. The mass average molecular weight here refers to the molecular weight measured in terms of polystyrene by a GPC (gel permeation chromatography) method.
[0044] The tackifier resin used in the rubber-based adhesive can be any of various types, but is preferably a petroleum-based resin, a terpene resin, or a coumarone resin. The tackifier resin may be used alone or in combination of two or more types, but it is preferable to use a petroleum-based resin in combination with at least one selected from a terpene resin and a coumarone resin. Such a combination of tackifier resins makes it easier to improve the adhesive strength. Examples of the petroleum resin include aliphatic petroleum resin (C5 petroleum resin), alicyclic petroleum resin, aromatic petroleum resin, etc., and from the viewpoint of compatibility with the styrene-isoprene block copolymer, aliphatic petroleum resin is preferred. In addition, it is preferable to use a petroleum resin having a softening point of about 90 to 120°C. The terpene resin may have a softening point of about 80 to 120° C., but from the viewpoint of ensuring adhesive strength, it is preferable that the softening point is less than 100° C. The coumarone resin used has a softening point of preferably 110 to 130° C., more preferably 115 to 125° C., in order to ensure cohesive strength.
[0045] The amount of the tackifier resin is preferably 60 to 250 parts by mass, more preferably 100 to 200 parts by mass, and even more preferably 110 to 180 parts by mass, per 100 parts by mass of the rubber component. By setting the amount of the tackifier resin within the above range, it is possible to improve the cohesive force and impart appropriate adhesive strength. When a petroleum-based resin is used in combination with at least one selected from a terpene resin and a coumarone resin, the amount of the petroleum-based resin is preferably 50 to 200 parts by mass, more preferably 60 to 150 parts by mass, and more preferably 60 to 110 parts by mass, relative to 100 parts by mass of the rubber component. On the other hand, the amount of the terpene resin is preferably 10 to 70 parts by mass, more preferably 20 to 60 parts by mass, and even more preferably 30 to 50 parts by mass, relative to 100 parts by mass of the rubber component. Furthermore, the amount of the coumarone resin is preferably 10 to 60 parts by mass, more preferably 15 to 50 parts by mass, and even more preferably 20 to 40 parts by mass, relative to 100 parts by mass of the rubber component. The rubber-based adhesive may contain the above-mentioned fine particles, like the acrylic-based adhesive, and may also contain a softener, an antioxidant, a filler, etc., as necessary.
[0046] <Urethane adhesive> The urethane-based adhesive is not particularly limited, and examples thereof include urethane resins obtained by reacting at least a polyol with a polyisocyanate compound. Examples of the polyol include polyether polyol, polyester polyol, polycarbonate polyol, polycaprolactone polyol, etc. Examples of the polyisocyanate compound include diphenylmethane diisocyanate, tolylene diisocyanate, hexamethylene diisocyanate, etc. These urethane adhesives may be used alone or in combination of two or more. In addition, as the urethane-based adhesive, a urethane resin obtained by reacting a polyurethane polyol with a polyfunctional isocyanate-based curing agent may be used. The polyurethane polyol may be a reaction product of the above-mentioned polyol with a polyisocyanate compound, or a reaction product of a polyol with a polyisocyanate compound and a chain extender such as a diamine. As the polyfunctional isocyanate-based curing agent, any compound having two or more isocyanate groups may be used, and the above-mentioned isocyanate compounds may be used. The urethane-based adhesive may contain the above-mentioned fine particles in addition to the urethane resin, and may also contain a tackifier resin, a softener, an antioxidant, a filler, etc., as necessary.
[0047] <Silicone-based adhesive> Examples of silicone-based adhesives include silicone-based adhesives of addition reaction type, peroxide curing type, or condensation reaction type. Among them, addition reaction type silicone-based adhesives are preferably used from the viewpoint of being curable at low temperature in a short time. The addition reaction type silicone-based adhesive is cured when the adhesive layer is formed. When an addition reaction type silicone-based adhesive is used as the silicone-based adhesive, the silicone-based adhesive may contain a catalyst such as a platinum catalyst. The silicone-based adhesive may contain fine particles, and may also contain a crosslinking agent and various additives for controlling adhesive strength.
[0048] <Thickness> The thickness of the adhesive layer is preferably 100 μm or more. By making the thickness 100 μm or more, the adhesive strength of the concrete repair tape can be further improved. From this viewpoint, the thickness of the adhesive layer is more preferably 250 μm or more, even more preferably 300 μm or more, and even more preferably 500 μm or more. In addition, the upper limit of the thickness of the adhesive layer is not particularly limited, but from the viewpoint of the deterioration of workability due to the weight increase while obtaining the effect of improving the adhesive strength of the concrete repair tape according to the thickness, it is, for example, 2000 μm, and 1200 μm or less is preferable.
[0049] <Coating film> The adhesive sheet used in the attachment step may further include a coating film provided on the surface opposite to the surface of the adhesive layer side of the substrate. This can further improve the weather resistance of the adhesive sheet used in the attachment step. Examples of paints for forming the coating film include fluorine-based paints and silicon-based paints. Among these paints, fluorine-based paints are preferred from the viewpoint of weather resistance. The coating film can be formed by applying the above-mentioned paint to the substrate and drying it as necessary.
[0050] From the viewpoint of weather resistance of the concrete repair tape of the present invention, the thickness of the coating film (dry) is preferably 25 μm or more, more preferably 30 μm or more, and further preferably 35 μm or more. The upper limit of the range of the coating film thickness is usually 60 μm.
[0051] (Thickness of adhesive sheet used in application process) The thickness of the adhesive sheet used in the attachment step is preferably 100 to 2500 μm. When the thickness of the adhesive sheet is 100 μm or more, the effect of the adhesive sheet in protecting the concrete can be further improved. When the thickness of the adhesive sheet is 2500 μm or less, the conformability to the surface of the concrete can be easily improved. From this viewpoint, the thickness of the adhesive sheet is more preferably 150 to 2000 μm, even more preferably 200 to 1800 μm, and even more preferably 400 to 1500 μm.
[0052] (Storage modulus of the adhesive layer of the adhesive sheet used in the application process) The storage modulus at 0°C of the adhesive layer of the adhesive sheet used in the attachment step is preferably 200,000 to 2,500,000 Pa. When the storage modulus at 0°C is within the above range, even in a low-temperature environment, when the adhesive layer is damaged by an external impact or the like, the force to restore the damaged area (hereinafter also referred to as self-repairing force) becomes strong. As a result, the protective performance for concrete is further improved. From this viewpoint, the storage modulus at 0°C of the adhesive layer of the adhesive sheet is more preferably 250,000 to 2,300,000 Pa, even more preferably 300,000 to 1,600,000 Pa, and even more preferably 350,000 to 1,200,000 Pa. The storage modulus at 0°C of the adhesive layer of the adhesive sheet can be measured by the method described in the Examples below.
[0053] (Structure of adhesive sheet used in application process) 1, the pressure-sensitive adhesive sheet 10 used in the attachment step is preferably a single-sided pressure-sensitive adhesive sheet having a substrate 12 and a pressure-sensitive adhesive layer 11 provided on one side of the substrate 12. This allows the pressure-sensitive adhesive layer 11 to be protected by the substrate 12. The adhesive sheet in each drawing is used by attaching surface 11A of adhesive layer 11 to concrete as an adhesive surface.
[0054] In order to improve the interfacial strength between the substrate 12 and the adhesive layer 11, as shown in FIG. 2, the adhesive sheet 10 may further include an undercoat layer 13 on the surface of the substrate 12 facing the adhesive layer.
[0055] In order to improve weather resistance, a coating film 14 may be further formed on the surface of the substrate 12 opposite to the surface on which the pressure-sensitive adhesive layer is formed, as shown in Fig. 3. In this case, the undercoat layer may be omitted.
[0056] The concrete protection method of the present invention is applied to the surface of a concrete structure. The concrete protection method of the present invention can suppress the progression of corrosion or damage to the concrete structure, or the occurrence of corrosion of the concrete structure from the damaged area. Examples of concrete structures include viaducts, tunnels, embankments, buildings, and other structures, mooring facilities in ports, utility poles, dams, and the like. The concrete structure may have a metal material such as steel material provided inside. When a concrete structure has a damaged area such as a crack, water may enter the damaged area and corrode the internal steel material, but by attaching the pressure-sensitive adhesive sheet of the present invention to the damaged area, water entry and the like can be prevented, and corrosion of the internal steel material can be prevented.
[0057] [Concrete protection kit] The concrete protection kit of the present invention is a concrete protection kit including a cleaning adhesive tape for cleaning concrete and an adhesive sheet for protecting concrete. The cleaning adhesive tape cleans the concrete by adhering to and removing dust adhering to the surface of the concrete from the surface of the concrete. The adhesive sheet protects the concrete by being attached to the surface of the concrete cleaned with the cleaning adhesive tape. By using the concrete protection kit of the present invention, the concrete protection method of the present invention can be easily carried out.
[0058] The cleaning adhesive tape and adhesive sheet have already been explained in the section on the concrete protection method, so explanation of the cleaning adhesive tape and adhesive sheet in the concrete protection kit of the present invention will be omitted.
[0059] The concrete protection kit of the present invention is used on the surface of a concrete structure. By using the concrete protection kit of the present invention, the progress of corrosion or damage to the concrete structure, or the occurrence of corrosion of the concrete structure from the damaged area, can be suppressed. Examples of concrete structures include viaducts, tunnels, embankments, buildings, and other structures, mooring facilities in ports, utility poles, dams, and the like. The concrete structure may have a metal material such as steel material provided inside. When a concrete structure has a damaged area such as a crack, water may enter the damaged area and corrode the internal steel material, but by attaching the pressure-sensitive adhesive sheet of the present invention to the damaged area, water entry and the like can be prevented, and corrosion of the internal steel material can be prevented. EXAMPLES
[0060] The present invention will be described in more detail below using examples, but the present invention is not limited to these examples.
[0061] [Evaluation method] In the examples and comparative examples, the pressure-sensitive adhesive sheets were evaluated by the following evaluation methods.
[0062] <Total light transmittance of oriented polypropylene tape (OPP tape)> An OPP tape (manufactured by Sekisui Chemical Co., Ltd., product name "Tough Light Tape No. 835") was processed to a size of 25 mm in width and 100 mm in length, and was attached to a mortar for evaluation (a mortar board (compliant with JIS R 5201) with a width of 150 mm × depth of 70 mm × height of 20 mm), and then a 2 kg roller was made to reciprocate twice. Then, 10 seconds after the 2 kg roller had reciprocated twice, the OPP tape was peeled off from the mortar for evaluation. The OPP tape peeled off from the mortar for evaluation was attached to the release surface of the following release PET (polyethylene terephthalate) film (thickness 50 μm) to prepare a measurement sample. Five measurement points were randomly selected along the length of the measurement sample, and the total light transmittance was measured at the selected measurement points in accordance with JIS K7361-1. The average of the total light transmittance at the five measurement points was taken as the total light transmittance of the measurement sample. The measurement conditions are as follows: The above OPP tape is a single-sided adhesive sheet having an adhesive layer made of an acrylic adhesive on one side of an OPP film. When the total light transmittance was measured as is without being attached to the evaluation mortar, the total light transmittance was 91%, and the 180° adhesive strength described below was 8 N / 25 mm. Release PET (polyethylene terephthalate) film: manufactured by Lintec Corporation, product name "PET5002", total light transmittance 92% (Measurement conditions) Measuring device: Haze meter (manufactured by Nippon Denshoku Industries Co., Ltd., product name "Haze Meter NDH4000") Measurement environment temperature: 23℃ Humidity of the measurement environment: 50%
[0063] <Visible light transmittance of oriented polypropylene tape> An OPP tape (manufactured by Sekisui Chemical Co., Ltd., product name "Tough Light Tape No. 835") was processed to a size of 25 mm in width and 100 mm in length, and was attached to a mortar for evaluation (a mortar board (compliant with JIS R 5201) with a width of 150 mm × depth of 70 mm × height of 20 mm), and then a 2 kg roller was made to reciprocate twice. Then, 10 seconds after the 2 kg roller had reciprocated twice, the OPP tape was peeled off from the mortar for evaluation. The OPP tape peeled off from the mortar for evaluation was attached to the release surface of the following release PET (polyethylene terephthalate) film (thickness 50 μm) to prepare a measurement sample. Five measurement points were randomly selected along the length of the measurement sample, and the visible light transmittance was measured at the selected measurement points using a handy transmittance meter, and the average of the visible light transmittance at the five measurement points was regarded as the visible light transmittance of the measurement sample. The measurement conditions are as follows: (Measurement conditions) Release PET (polyethylene terephthalate) film: manufactured by Lintec Corporation, product name "PET5002", visible light transmittance 92% Handy transmittance meter: Visible light transmittance measuring device (manufactured by Sato Shoji Co., Ltd., product name "Tint Meter TM2000 Satotec") Measurement environment temperature: 23℃ Humidity of the measurement environment: 50%
[0064] <Tensile load difference> The cleaning adhesive tape used in each Example and Comparative Example was measured for the tensile load when pulled 2.5% and 0.5% using a tensile tester in an environment of 23° C., and the difference between the tensile loads was calculated. The measurement conditions are as follows: (Measurement conditions) Tensile testing machine: A&D Co., Ltd., product name "Tensilon Universal Material Testing Machine" Sample size: width 24mm x length 80mm Chuck distance: 50mm Tensile speed: 300mm / min
[0065] <Gel fraction> The adhesive layer of the cleaning adhesive tape was collected in an amount of W1 (g), immersed in an organic solvent at 23°C for 24 hours, and the insoluble matter was filtered through a 200-mesh wire net. The residue on the wire net was dried by heating at 110°C, and the weight W2 (g) of the resulting dried residue was measured. The gel fraction (degree of crosslinking) was calculated using the following formula (2). As the organic solvent, a solvent capable of dissolving uncrosslinked polymers among the polymers constituting the adhesive layer may be selected, and when the adhesive layer is formed of an adhesive composition containing an acrylic polymer, for example, toluene or tetrahydrofuran (THF) may be used. Gel fraction (mass%) = 100 × W2 / W1 (2)
[0066] <180°adhesion> The adhesive strength was determined by measuring the 180° peel adhesion to a SUS 304 steel plate according to the method of JIS Z 0237.
[0067] <Storage modulus at 0℃> The storage modulus of the adhesive layer of the adhesive sheet at 0°C was calculated by measuring the dynamic viscoelasticity spectrum using a dynamic viscoelasticity measuring device (manufactured by IT Measurement & Control Co., Ltd., product name "DVA-200") under the following conditions: shear mode: 10 Hz, strain: 0.1%, temperature range: -100°C to 100°C, heating rate: 10°C / min.
[0068] <90°adhesion> A film was laminated on the adhesive used in the adhesive layer of the adhesive sheet of each Example and Comparative Example to prepare a measurement adhesive sheet having a film and an adhesive layer on one side of the film. The film may be a film that is difficult to stretch so that it is not broken at the interface between the film and the glue during the adhesive strength measurement. In this measurement, a primer-treated PET film was used. The obtained measurement adhesive sheet was cut to a width of 25 mm and a length of 100 mm to prepare a measurement sample. The measurement sample was attached to the following standard mortar plate through the adhesive layer in an environment of 0°C and 50 RH%, and cured for 3 days in an environment of 0°C and 50 RH%. In addition, when attaching to the mortar, a 2 kg roller was made to reciprocate twice at a speed of 10±0.5 mm / s. Then, the measurement sample that had been cured for 3 days was fixed to the chuck of a tensile tester (manufactured by A&D Co., Ltd., product name "Tensilon Universal Material Tester"). Then, in an environment of 0°C and 50% RH, the adhesive sheet was pulled 60 mm or more at a peel angle of 90° and a speed of 300 mm / min, and the average value of the load (N) detected by the load cell was recorded and used as the 90° adhesive strength. (Standard mortar board) The standard mortar plate is a mortar plate used for measuring the value of b in the above formula (1). The standard mortar plate was prepared as follows. A mortar board (compliant with JIS R 5201, width 70 mm, length 150 mm) was prepared. Dust attached to the surface of the prepared mortar board was removed using masking tape. At this time, OPP tape (manufactured by Sekisui Chemical Co., Ltd., product name "Tough Light Tape No. 835") was attached to the surface of the mortar board, and the OPP tape was peeled off from the surface of the mortar board. The OPP tape was then attached to the release surface of a release PET (polyethylene terephthalate) film (thickness 50 μm) to prepare a sample, and dust was removed until the total light transmittance reached 87%. The mortar board from which dust had been removed as described above was used as a reference mortar board, and the 90° adhesive force of the reference mortar board was measured, and the measured value was taken as the value of b.
[0069] <Practical evaluation> The adhesive sheet obtained in each Example and Comparative Example was cut to a size of 25 mm wide and 100 mm long, and then bonded to a SUS plate (50 mm wide and 125 mm long) via the adhesive layer to prepare a measurement sample. When bonding to the SUS plate, a 2 kg roller was reciprocated twice at a speed of 10±0.5 mm / s. The measurement sample was then fixed to the chuck of a tensile tester (manufactured by A&D Co., Ltd., product name "Tensilon Universal Material Tester"). Thereafter, in an environment of 0°C and 50 RH%, the adhesive sheet was pulled 60 mm or more at a peel angle of 90° and a speed of 300 mm / min, and the average value of the load (N) detected by the load cell was recorded, and this was taken as the 90° adhesive force to the stainless steel plate. Evaluation was then performed according to the following evaluation criteria. ◎: Adhesive strength is 30N / 25mm or more 〇: Adhesive strength is 20N / 25mm or more and less than 30N / 25mm ×: Adhesive strength is less than 20N / 25mm Normally, to determine the level of adhesive strength that will not peel off in practical use, a practical evaluation using water spray is performed as described below. However, because water freezes in low-temperature environments, the practical evaluation using the 90° adhesive strength described above was substituted for the practical evaluation using water spray. (Practical evaluation using water injection) Adhesive sheets (25 mm wide, 100 mm long) with the adhesive strength of the examples and comparative examples are attached to a SUS plate (50 mm wide, 125 mm long) and cured at 23°C for 3 days to prepare an evaluation sample. Water is sprayed for 5 minutes from a spray position diagonally above the evaluation sample toward the end side of the longitudinal direction of the evaluation sample under a water pressure of 8 MPa. The position where water is sprayed (spray position) is a position where the angle between the line connecting the spray position and the center part of the evaluation sample end and the SUS plate is 30°, and the position is directly above a point 5 cm horizontally away from the center part of the adhesive sheet end. The peeled distance of the evaluation sample after water spraying is measured and evaluated according to the following criteria. ◎: Peel distance is 0mm or more and less than 15mm ○: Peeling distance is 15mm or more but less than 25mm ×: Peeling distance is 25mm or more Based on many years of experience, it is known that an evaluation result of "◎" for the above-mentioned 90° adhesive strength corresponds to an evaluation result of "◎" in the above-mentioned water jet evaluation, an evaluation result of "○" for the above-mentioned 90° adhesive strength corresponds to an evaluation result of "○" in the above-mentioned water jet evaluation, and an evaluation result of "×" for the above-mentioned 90° adhesive strength corresponds to an evaluation result of "×" in the above-mentioned water jet evaluation.
[0070] [Materials used] In each of the examples and comparative examples, the following materials were used.
[0071] <Cleaning adhesive tape> Tape A: Masking tape (manufactured by Sekisui Chemical Co., Ltd., product name "Rubber Mat Fixing Tape"), base material (OPP film), adhesive layer adhesive (acrylic adhesive) Tape B: Airtight waterproof tape (manufactured by Sekisui Chemical Co., Ltd., product name "No. 740"), base material (PET fabric), adhesive for adhesive layer (acrylic adhesive) Tape C: Masking tape (manufactured by Sekisui Chemical Co., Ltd., product name "Fitlite Tape Strong Adhesive No. 736"), base material (PET fabric), adhesive layer adhesive (acrylic adhesive) Tape D: Masking tape (manufactured by Sekisui Chemical Co., Ltd., product name "Fitlite Tape No. 738"), base material (PET fabric), adhesive layer adhesive (acrylic adhesive)
[0072] <Adhesive layer of adhesive sheet> 2-Ethylhexyl acrylate n-Butyl acrylate Acrylic Acid Acryloylmorpholine Dimethylacrylamide Olefin polymer: Product name "L-1253", manufactured by Kuraray Co., Ltd., hydrogenated polybutadiene having a (meth)acryloyl group at one end Crosslinking agent: Product name "TEAI-1000", manufactured by Nippon Soda Co., Ltd. Tackifier resin 1: Product name "Alcon P140", manufactured by Arakawa Chemical Industries, Ltd., hydrogenated petroleum resin, softening point 140°C Tackifier resin 2: Product name "Alcon P100", manufactured by Arakawa Chemical Industries, Ltd., hydrogenated petroleum resin, softening point 100°C Polymerization initiator: 2,2-dimethoxy-2-phenylacetophenone
[0073] [Preparation of Pressure-Sensitive Adhesive Sheets of Examples 1 to 13 and Comparative Examples 1 to 4] Pressure-sensitive adhesive compositions were prepared according to the formulations shown in Tables 1 to 3. In Tables 1 to 3, "parts" refers to "parts by mass." Nitrogen was purged into the pressure-sensitive adhesive composition to remove dissolved oxygen. Next, a spacer having the same thickness as the thickness of the pressure-sensitive adhesive layer was placed on the release-treated surface of the release sheet, and the pressure-sensitive adhesive composition was applied onto the release-treated surface of the release sheet. Next, another release sheet was covered on the applied pressure-sensitive adhesive composition so that the release-treated surface was in contact with the pressure-sensitive adhesive composition. As the release sheet, a silicone release-treated PET film (thickness 50 μm) was used. In this state, the ultraviolet irradiation intensity on the release sheet on the coated side is 5 mW / cm 2 The lamp intensity of the chemical lamp was adjusted so that the ultraviolet light was irradiated from one side for 15 minutes, thereby obtaining an adhesive layer consisting of a single adhesive layer with release sheets attached to both sides. Then, one of the release sheets was peeled off, and a primer-treated PET film (thickness: 50 μm) was attached to the adhesive layer obtained by the above method to obtain an adhesive sheet. The other release sheet was also peeled off from the adhesive sheet before various physical properties or evaluations were performed.
[0074] [Table 1]
[0075] [Table 2]
[0076] [Table 3]
[0077] From the above examples, it was found that by carrying out cleaning until the relationship of the above-mentioned formula (1) is satisfied, it is possible to properly remove dust adhering to the surface of concrete in a low temperature environment before attaching the adhesive sheet to the surface of concrete. On the other hand, from the above comparative examples, it was found that unless cleaning is carried out until the relationship of the above-mentioned formula (1) is satisfied, the work of removing dust adhering to the concrete surface before attaching the adhesive sheet to the concrete surface in a low temperature environment will be insufficient. [Explanation of symbols]
[0078] 10 Adhesive sheet 11 Adhesive layer 12 Base material 13 Undercoat layer 14 Coating
Claims
1. A method for protecting concrete by attaching an adhesive sheet to the concrete, comprising: a cleaning step of cleaning the surface of the concrete to which the adhesive sheet is to be attached, and removing dust adhering to the surface from the surface; and The method includes a step of attaching the adhesive sheet to the surface of the concrete cleaned by the cleaning step, The cleaning step is a concrete protection method in which an oriented polypropylene tape having a total light transmittance of 86% or more is attached to a surface of the concrete, and cleaning is performed until the relationship of the following formula (1) is satisfied, where the visible light transmittance of the oriented polypropylene tape after the oriented polypropylene tape is peeled off from the surface of the concrete is a%, and the 90° adhesive strength of the adhesive sheet to a mortar board at a temperature of 0°C in accordance with JIS R 5201 is bN / 25 mm. a+b≧110 (1)
2. 2. The method for protecting concrete according to claim 1, wherein the visible light transmittance of the oriented polypropylene tape is measured by a handy transmittance meter.
3. 2. The concrete protection method according to claim 1, wherein the surface of the concrete before the cleaning process is covered with an oriented polypropylene tape having a total light transmittance of 86% or more, and the total light transmittance of the oriented polypropylene tape after the tape is peeled off is 80% or less.
4. 2. The concrete protection method according to claim 1, wherein the cleaning step comprises removing the dust adhering to the surface of the concrete by adhering the dust to an adhesive cleaning tape having an adhesive layer.
5. The method for protecting concrete according to claim 4, wherein the thickness of the adhesive layer of the cleaning adhesive tape is 20 to 80 μm.
6. The method for protecting concrete according to claim 4, wherein the adhesive layer of the cleaning adhesive tape has a gel fraction of 70% or less.
7. 5. The method for protecting concrete according to claim 4, wherein the difference between the tensile load when the cleaning adhesive tape is elongated by 2.5% and the tensile load when the cleaning adhesive tape is elongated by 0.5% is 40 N / 24 mm or less.
8. 5. The method for protecting concrete according to claim 4, wherein the cleaning adhesive tape has a 180° adhesive strength of 5 N / 25 mm or more.
9. 2. The method for protecting concrete according to claim 1, wherein the thickness of the adhesive sheet is 100 to 2500 μm.
10. The pressure-sensitive adhesive sheet includes a pressure-sensitive adhesive layer, The method for protecting concrete according to claim 1, wherein the storage modulus of the adhesive layer of the adhesive sheet at 0° C. is 200,000 to 2,500,000 Pa.
11. A concrete protection kit including a cleaning adhesive tape for cleaning concrete and an adhesive sheet for protecting the concrete, The cleaning adhesive tape adheres to and removes dust adhering to the surface of the concrete, thereby cleaning the concrete; The adhesive sheet is a concrete protection kit that protects the concrete by being attached to the surface of the concrete that has been cleaned with the cleaning adhesive tape.
Citation Information
Patent Citations
Structure protection sheet and method for manufacturing reinforced structure
JP2022184760A